Lessons from CTA's CSA project in Southern Africa - Ajayi, Oluyede C. (Technical Centre for Agricultural and Rural Cooperation, 2019)
Olu Ajayi, Senior Programme Coordinator (Agriculture and Climate Change) at CTA, shares the results achieved and lessons learned from the project on Scaling up Climate Smart Agriculture solutions for Cereal and Livestock farmers in Southern African Region.